دور بعض الممارسات الزراعية في زيادة الكفاءة الإنتاجية لدى بعض أصناف القمح تحت ظروف الزراعة المطرية - Janoud, Gada Damen; AL-Ouda, Ayman Shehada; Al-mahasna, Hussain (Latakia University Journal -Biological Sciences Series, 2013)
نُفذت تجربة حقلية في محطة بحوث إزرع، بمحافظة درعا، في سورية، خلال الموسمين الزراعيين 2010/2011، و2011/2012، بهدف تقويم دور بعض الممارسات الزراعية في تحسين أداء بعض أصناف القمح القاسي (دوما1، ودوما3)، والطري (دوما2، ودوما4)، تحت ظروف الزراعة المطرية. وضعت التجربة وفق تصميم القطاعات العشوائية الكاملة العاملية المنشقة، بواقع ثلاثة مكررات. كان متوسط قوة النمو الأولي، ومتوسط مساحة الورقة العلمية، ومتوسط طول حامل السنبلة، ومتوسط دليل المساحة الورقية الأعلى معنوياً خلال الموسم الزراعي الأول الأكثر هطولاً لدى نباتات صنف القمح الطري دوما4 عند موعد الزراعة الأول، ومعدل التسميد الآزوتي (150 كغN. هكتار1-)، وعند إضافة السماد الآزوتي على دفعتين(1.6ـ 2.5،53.4 سم2،16.3سم، 1.20على التوالي)، في حين كانت تلك الصفات تباعاً الأدنى معنوياً خلال الموسم الزراعي الثاني الأكثر جفافاً، لدى نباتات صنف القمح القاسي دوما3، بالنسبة إلى صفات قوة النمو الأولي، وطول حامل السنبلة، ودليل المساحة الورقية ولدى الصنف دوما2 بالنسبة إلى صفة مساحة الورقة العلمية، عند الزراعة المتأخر جداً (15كانون الثاني)، في المعاملة الشاهد (دون تسميد آزوتي) (3.6ـ4.5، 3.3سم،0.18، 16.6، سم2 على التوالي). وكان متوسط الغلة الحبية الأعلى معنوياً خلال الموسم الزراعي الأول لدى صنفي القمح الطري دوما4، ودوما2 عند موعد الزراعة الأول ومعدل التسميد الآزوتي (200 كغ. هكتار-1) عند إضافة الأسمدة الآزوتية على دفعتين (660.4، 631.1 غ. م-2 على التوالي)، في حين كان الأدنى معنوياً خلال الموسم الزراعي الثاني لدى نباتات صنف القمح القاسي دوما1 في المعاملة الشاهد (دون تسميد آزوتي) (127غ. م-2). يُسهم ضبط بعض الممارسات الزراعية المهمة في تحسين غلة محصول القمح الحبية، نتيجة تحسين الصفات المورفوفسيولوجية المرتبطة بالغلة، وخاصةً حجم المصدر الفعّال في عملية التمثيل الضوئي (دليل المساحة الورقية، مساحة الورقة العلمية). وكانت استجابة أصناف القمح الطري أفضل بالمقارنة مع القمح القاسي، ما يشير إلى أهمية تحسين عوامل إدارة المحصول لبلوغ طاقة الطراز الوراثية الإنتاجية الكامنة. A field experiment was conducted during the two consecutive growing seasons (2010/2011 and 2011/2012) at Ezra’ Research Station/Deraa/Syria in order to evaluate the role of some agricultural practices in improving the performance of four wheat varieties (Acsad1105, Acsad1229, Acsad885 and Acsad901) under rainfed conditions. The experiment was laid according to factorial randomized complete block-split design with three replications. The mean average of early vigor, flag leaf area, peduncle length and leaf area index was significantly higher during the first growing season for the wheat variety (Acsad901) at the first planting date with a nitrogen amount of (150 kgN. Hectar1), and when nitrogen fertilizers were added twice (1.6-2.5, 53.4cm2, 16.3cm, 1.20 respectively). The mean average of the same studied aspects, however, was significantly lower during the second growing season in the case of the variety Acsad855 with regards to the early vigor, as well as in the case of the variety Acsad1129 in the case of the leaf area Flag at a late planting date, and without nitrogen fertilizers (3.6ـ 4.5, 3.3 cm, 0.18, 16.6 cm2 respectively). The mean average of the grain yield was significantly higher during the first growing season for two wheat varieties (Acsad901, Acsad1229) at the first planting date, nitrogen rate 200 kgN. Ha-1, and when nitrogen fertilizers were added twice (660.4, 631.1 g.m-2 respectively), while it was significantly lower during the second growing season for the variety Acsad1105, at a late planting date, and without nitrogen fertilizers (127 g.m-2). Optimizing some important cultural practices helps increasing wheat grain yield by improving morpho-physiological traits related to yield particularly the size of source photo synthise (Leaf Area Index, Flag leaf area). The response of astivum wheat variety was better compared to durum wheat. This shows the importance of improving crop mangment factors in order to reach the maximum potential yield.